THE DETERMINANTS INFLUENCING BEHAVIORIAL INTENTION TO USE E-WALLET DURING COVID-19 PANDEMIC IN MANADO - Rantung, Hermi Monica; Tumbuan, Alfa J.F.A; Gunawan, Emilia M. (Universitas Sam Ratulangi, 2020)
Abstract: Currently many e-wallets have been developed, one of them is go-pay which is part of go-jek application. Since the Covid-19 pandemic is in Indonesia on March 2020, e-wallets help users make payments without having to make direct physical contact with the seller and people will no need to carry cash which can also be a means of transmission of covid-19. The purpose of this study is to find out whether the variables which are perceived trust, perceived usefulness, and perceived ease of use can influence the behavioral intention of go-pay users. This study uses a quantitative method with a questionnaire to collect the data and multiple linear regression as a tool to analyze the data that has been collected. The findings of this study showed that perceived trust and perceived ease of use have positive and significant influence on behavioral intention, while perceived usefulness has no influence and not significantly on behavioral intention. From the research results; marketers or company must maintain the quality of Go-Pay system so there will not be any errors when people used the application as a payment instrument.Â Keywords: perceived trust, perceived usefulness, perceived ease of use, behavioral intention